Expand and simplify (1+2z-5x)(z+5x-7) and (1-a+2x^2)^2  

1 Answer | Add Yours

justaguide's profile pic

Posted on

Th expressions to be expanded and simplified are (1+2z-5x)(z+5x-7) and (1-a+2x^2)^2

(1+2z-5x)(z+5x-7)

=> z + 5x - 7 + 2z(z+5x-7) - 5x(z+5x-7)

=> z + 5x - 7 + 2z^2 + 10zx - 14z - 5zx - 25x^2 + 35x

=> 2z^2 - 25x^2 + 5zx + 40x - 13z - 7

(1-a+2x^2)^2

=> 1 + a^2 + 4x^4 - 2a - 4ax^2 + 4x^2

=> 4x^4 + a^2 - 4ax^2 + 4x^2 - 2a + 1

The required results are (1+2z-5x)(z+5x-7) = 2z^2 - 25x^2 + 5zx + 40x - 13z - 7 and (1-a+2x^2)^2 = 4x^4 + a^2 - 4ax^2 + 4x^2 - 2a + 1

We’ve answered 331,187 questions. We can answer yours, too.

Ask a question